A new, to date endemic, family of dragonfly in the mid-Cretaceous fossil fish Konservat-Lagerstätte of Haqel, Lebanon (Odonata: Anisoptera) - Azar, Dany; Maksoud, Sibelle; Abi-Saad, Pierre; Nel, Andre (Zootaxa, 2024)
The new family Libanoaeshnidae fam. nov., with the new genus and species Libanoaeshna mikhaeli gen. et sp. nov., are characterised, described and illustrated from Haqel, the famous upper Cenomanian fossil fish outcrop of Lebanon. This is the first time that a fossil insect is reported from this site. Libanoaeshnidae fam. nov., together with three other Cretaceous families, can be included in the stem group of the modern Aeshnodea Bechly, 1996, confirming the important diversification of this clade during this period, even if the oldest known representatives of the Aeshnidae sensu stricto are still Eocene.